Shariah Governance Matters: Analysis of Enterprise Risk Management and Risk Performance in Indonesian Islamic Banks - Ita Sitasari Tuhari; Muhammadtahir Cheumar; Hardius Usman (Kirana Publisher (KNPub), 2026)
This study investigates the influence of the five components of the Committee of Sponsoring Organisations of the Treadway Commission Enterprise Risk Management (COSO ERM) framework on bank risk performance. It examines the moderating role of Shariah governance in Indonesian Islamic banks. Using a quantitative cross-sectional approach, data were collected from 180 managers and senior officers of full-fledged Islamic commercial banks and analysed through partial least squares structural equation modelling. The findings show that governance and culture, strategy and objective setting, performance, and information, communication and reporting significantly improve bank risk performance. At the same time, review and revision have no direct significant effect. Shariah governance does not moderate relationships among individual ERM components but strengthens the effect of integrated ERM on risk performance. The study highlights that Shariah governance creates greater value when embedded within enterprise-wide risk management systems, providing implications for boards, regulators, and Islamic banking practitioners